2020
DOI: 10.24331/ijere.650861
|View full text |Cite
|
Sign up to set email alerts
|

Validating a Home Numeracy Questionnaire in Ecuador Using Factor Analysis

Abstract: The home numeracy questionnaire (HNQ) developed by LeFevre et al. (2009) is a self-report instrument to assess the home numeracy of young children. In this questionnaire, young children's parents have to indicate how often their child participates both in direct (e.g., counting down: 10, 9, 8, …) and indirect numeracy activities (e.g., playing board games with die or spinner). Based on a principal component analysis, LeFevre and colleagues found a four factor structure of the HNQ. Using a sample of 176 Ecuador… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Some studies have assumed the HME to be a unidimensional construct ( Blevins-Knabe and Musun-Miller, 1996 ) or identified a unidimensional construct through exploratory factor analysis ( Blevins-Knabe and Musun-Miller, 1996 ; Kleemans et al, 2012 ). Other studies have shown the HME is multi-dimensional through exploratory factor analyses ( LeFevre et al, 2009 , 2010 ; Dearing et al, 2012 ; Manolitsis et al, 2013 ) or by using confirmatory factor analysis to test the model fit of one potential model ( Van Hoof et al, 2020 ). However, only Hart et al (2016) have explicitly contrasted multiple potential factor structures to examine the best-fitting factor structure.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have assumed the HME to be a unidimensional construct ( Blevins-Knabe and Musun-Miller, 1996 ) or identified a unidimensional construct through exploratory factor analysis ( Blevins-Knabe and Musun-Miller, 1996 ; Kleemans et al, 2012 ). Other studies have shown the HME is multi-dimensional through exploratory factor analyses ( LeFevre et al, 2009 , 2010 ; Dearing et al, 2012 ; Manolitsis et al, 2013 ) or by using confirmatory factor analysis to test the model fit of one potential model ( Van Hoof et al, 2020 ). However, only Hart et al (2016) have explicitly contrasted multiple potential factor structures to examine the best-fitting factor structure.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have assumed the HME to be a unidimensional construct or identified a unidimensional construct through exploratory factor analysis (Blevins-Knabe and Musun . Other studies have shown the HME is multi-dimensional through exploratory factor analyses or by using confirmatory factor analysis to test the model fit of one potential model (Van Hoof et al, 2020). However, only have explicitly contrasted multiple potential factor structures to examine the best-fitting factor structure.…”
Section: Structure Of the Home Mathematics Environmentmentioning
confidence: 99%